Rapid changes in spectral composition after darkness influences nitric oxide, glucose and hydrogen peroxide production in the Antarctic diatom Fragilariopsis cylindrus - Fraser Kennedy; Martin, A; Andrew McMinn (2021)
Ice-associated phototrophic taxa contribute significantly to Antarctic primary production and are crucial to ecosystem stability in the Southern Ocean. The quantity and quality of light required for photosynthesis is the single most influential driver of ice-associated algal communities. While the presence of ice and snow greatly reduces the irradiance reaching the ice-water interface, it is also the spectral quality that influences the phototrophy of ice-associated microalgae communities. Here we test the capability of three electrochemical microsensors to detect photosynthetically derived “stress” metabolites produced by the Antarctic diatom F. cylindrus. Following a period of dark incubation, this photo-physiological response differed with respect to the intensity and spectral quality of light during re-illumination. Exposure to blue light resulted in impairment in photosynthetic efficiency of PS II ( F v / F m ) and resulted in the production of nitric oxide (NO), hydrogen peroxide (H 2 O 2 ) and glucose exudation. A similar trend in metabolite production was observed when subjected to white light, but not during red or green illumination. These results indicate that rapid exposure to light and variation in spectral composition can cause significant stress that can be quantified using H 2 O 2 , NO and glucose microsensors. This metabolic overflow was triggered by the disruption of normal photosynthetic electron flow and it is proposed that the detection of extracellular metabolites can be directly attributed to intracellular activity.